O07.3 A Psychological Experiment to Examine the Global Impact of Stigma on Individuals Diagnosed with Type 1 Herpes Simplex Virus (HSV-1). (13th July 2013) - Whale, J; Clarke, E; Patel, N; Graham, C; Ingham, R; Patel, R
Abstract : Background: HSV-1 causes at least 50% of primary genital herpes infections in Europe, Canada, Australia and the USA. In the UK, rates may be even higher, as the level 3 STI clinic in Southampton observes approximately 80% of primary genital herpes infections in young women are due to HSV-1. Regardless of location, individuals disclosing genital herpes infection may experience enacted stigma associated with negative stereotypes of sexual immorality. Patients may often fear rejection and conceal their HSV status, deleteriously affecting social relationships and self-identity. Our study aimed to assess whether a relationship could be established between female HSV-1 infected status and sexual attractiveness to males, and whether a significant difference existed between male responses to HSV-1 orolabial and genital herpes infection disclosures by females. Methods: The study was a randomised controlled trial of 111 male participants, recruited from university undergraduate students. Participants were randomly allocated to 1 of 3 groups and shown discrete video scenarios of a female actress disclosing HSV-1 infection. Group-specific questionnaires yielded quantitative data from visual analogue scales measuring attractiveness and truthfulness regarding disclosure. Results: Pilot data showed that there may be a significant reduction in female attractiveness to males, associated with HSV-1 genital herpes disclosure, but not following HSV-1 orolabial herpes disclosure. Pilot data showed there may be a significant reduction in male's perceived truthfulness of HSV-1 orolabial herpes disclosure by females, in place of HSV-1 genital herpes. A full complement of results will be available by the ISSTDR/IUSTI conference. Conclusion: Female patients diagnosed with HSV-1 genital herpes are often advised by clinicians that strategic disclosure of orolabial herpes will maintain role relationships with male partners. However, our findings show that orolabial herpes disclosure may negatively affect relationships, as male partners may perceive such disclosure to be significantly less truthful than genital herpes disclosure.